2004
DOI: 10.1149/1.1644605
|View full text |Cite
|
Sign up to set email alerts
|

Zirconium Behavior in Molten LiCl-KCl Eutectic

Abstract: Some oxidation states ͑0, ϩ1, ϩ2, and ϩ4͒ of zirconium exist in a LiCl-KCl eutectic system over the temperature range 450-550°C, and the behavior is complicated. In cyclic voltammograms at 500°C, a cathodic peak was observed at about Ϫ1.2 V vs. Ag/AgCl reference electrode, which might be due to the reduction of Zr͑IV͒ to ZrCl and zirconium metal. Two anodic peaks might correspond to the oxidation of ZrCl and zirconium metal, respectively. The electrolysis at a cathode potential of about Ϫ1.1 V yielded a nodula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
130
1
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 87 publications
(139 citation statements)
references
References 13 publications
6
130
1
2
Order By: Relevance
“…Their corresponding anodic peaks C and E are found at around À0.85 and À0.78 V, respectively. The electrochemical behavior of Zr(IV) in LiCl-KCl melt has been studied by several investigators [2,5,7,9,23]. Sakamura [7] assumed that the reduction peaks E 0 , C 0 , D 0 are corresponding to the reactions given in equations (2),(3), (4) and (6), respectively.…”
Section: Replacement Reaction Processmentioning
confidence: 99%
See 1 more Smart Citation
“…Their corresponding anodic peaks C and E are found at around À0.85 and À0.78 V, respectively. The electrochemical behavior of Zr(IV) in LiCl-KCl melt has been studied by several investigators [2,5,7,9,23]. Sakamura [7] assumed that the reduction peaks E 0 , C 0 , D 0 are corresponding to the reactions given in equations (2),(3), (4) and (6), respectively.…”
Section: Replacement Reaction Processmentioning
confidence: 99%
“…The chosen of the liquid alloy anode can not only reduce the operating temperature, but also expect to provide a low cost and semi-continuous process for production nuclear grade zirconium. The electrorefining and electrochemical process of Zr has been studied in various molten salt systems, including all-chloride baths such as LiCl-KCl-ZrCl 4 [2,[5][6][7], KCl-ZrCl 4 [8,9], all-fluoride baths such as LiF-NaF-KF-ZrF 4 and K 2 ZrF 6 [10,11], LiF-KF-ZrF 4 [3], LiF-CaF 2 -ZrF 4 [12] and chloridefluoride-mixed baths such as KCl-NaCl-ZrF 4 [13], KCl-NaCl-K 2 ZrF 6 [8,13,14], and LiCl-KCl-K 2 ZrF 6 [15] at temperature ranges of 450 C to 750 C. However, the operating temperature of the all-fluoride baths is 100 C $ 200 C higher, and the corrosion issue is more severe compared to those of all-chloride baths. In consideration of the melting point of liquid alloy anode and a moderate experimental condition, the Zr electrorefining process is proposed in LiCl-KCl-ZrCl 4 molten salt at 500 C in the initial stage of research.…”
Section: Introductionmentioning
confidence: 99%
“…Shiomi et al formed a bright Al-Zr alloy coating in dimethylsulfone-based melt containing AlCl 3 and reported that the pitting potential of Al 96.5 Zr 3.5 alloy shifted about +0.1 V compared with pure aluminum in 0.1 M NaCl solution [5]. The reduction reactions of zirconium ions are complicated as zirconium has valences from two to four in the ionic state, and Sakamura reported disproportional reactions between metallic zirconium and Zr(IV), and between Zr(IV) and Zr(II) in LiCl-KCl eutectic melts at 773 K [6].…”
Section: Introductionmentioning
confidence: 99%
“…While Sakamura Y. [4] found that in LiCl-KCl eutectic the Zr 4+ is reduced to ZrCl and zirconium metal, zirconium metal reacted with Zr 4+ to give Zr 2+ , and Zr 2+ is easily disproportionated into Zr 4+ and zirconium metal. Swaroop et al [5] considered Zr 4+ in NaCl-KCl is reduced in the three-step transfer of Zr 4+ → Zr 3+ → Zr 2+ → Zr at 943 to 1013 K. Ghosh et al [6] discovered that the electrochemistry process of Zr 4+ in LiCl-KCl eutectic in the range of 773 to 848 K is complex, as it involves multiple oxidation states and adsorption of electroactive spaces, and considered that the reduction of Zr 4+ to Zr is a two-electron transfer process involving the formation of Zr 2+ .…”
Section: Introductionmentioning
confidence: 99%
“…The molten salt electrochemistry of zirconium in alkali chloride and chloride-fluoride systems has been investigated by several researchers [1][2][3][4][5][6][7], but the electrochemical reduction mechanisms presented by different authors are dissimilar.…”
Section: Introductionmentioning
confidence: 99%